The Not-So-Mean Streets of Hangzhou, China: Reflecting with Nietzsche, Freud and Marx: A Commentary on Shaw, D. B. (2017). Posthuman Urbanism: Mapping Bodies in Contemporary City Space. Rowman & Littlefield - Steinbuch, Thomas (Journal of Posthumanism, 2024)
The study of the city is one of the most challenging topics we explore as philosophers, but it is highly rewarding because the city is our most complex cultural artifact and draws in so many aspects of cultural studies. Posthuman Urbanism: Mapping Bodies in Contemporary City Space (Shaw, 2017), does not disappoint in this respect of revealing how the city is the locus of so much of our neoliberal, and now neocolonial, culture of privilege in forms of classism, racism and genderism, and how the many “others” to these are relegated to the margins of city spaces so that the city becomes a de facto selection tool of sorting these into strata.